E-compare of Soccer Tournament Structures - Mat Yusof, Muhammad; Khalid, Ruzelan; Sulaiman, Tajularipin; Abdul Hamid, Mohamad Shukri; Mansor, Rosnalini; Che Rosli, Nurzahidah (2016)
This paper develops a system integrating the knowledge of statistical modeling and Monte Carlo simulation to evaluate various types of soccer tournament structures. A system called as “E-compare of Soccer Tournament Structures” aims to assist decision makers to choose the competitive soccer design.The system reports various tournaments metrics such as the expected number of goals scored and conceded, the expected number of wins, draws, and losses, and the expected final ranking at the end of the tournament.Based on a large number of simulations using teams participated in the Malaysian soccer super league, our analysis showed that different designs gave different impacts on the final ranking of the teams.Round robin is found to be the best structure in terms of identifying the strongest team to win the league compared to a knockout structure.